ELECTROMAGNETIC WAVE INTERACTIONS WITH MULTIPLE ARBITRARILY SHAPED NANOTUBES - Ashirmametov, Ravil; Faizulla, Aidana; Aznabayev, Abzal (Nazarbayev University School of Engineering and Digital Sciences, 2024)
This work studies the interaction of electromagnetic waves with arbitrarily shaped nanotubes. The research starts with the analysis of cylindrical-shaped nanotubes, due to their simplicity, further replacing them with arbitrary-shaped nanotubes for the same conditions. In this work, the objective is to increase the concentration of the electric field inside pairs of nanotubes by optimizing their shape appropriately. The Isogeometric- Analysis-based Boundary Element Method (IGABEM) approach was used to achieve the objective in pair with optimization approaches involving gradient-based and guided random search methods. This combination of mathematical programming with an appropriate parametric model, for the accurate modeling of free-form boundaries, and the IGABEM method for the shapes’ performance evaluation was successful in identifying the optimal shape of nanotubes. So far obtained results show a substantial increase in the concentration of electric field inside the shape-optimized nanotubes. A field concentration increase of more than 20 times compared to circular nanotubes was achieved and minimization showed 57 times decrease. Furthermore, the optimized shapes showed a better field concentration over a wide range of EM wave orientations and distances between nanotubes. This result demonstrates the robustness of the obtained results and their potential applicability in a wide range of applications.
Keywords: nanotubes; optimization; IGABEM; NURBS; Boundary Element Method; electromangetic waves; Type of access: Embargo